2009
DOI: 10.1017/s1751731109004558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein and energy supplementation on growth, forage intake, forage digestion and nitrogen balance in meat goat kids

Abstract: The objective of this study was to further the understanding of the effects of dietary protein and energy supplements on growth, performance, feed intake and grass forage digestibility in growing meat goat wethers. In Experiment 1, an 18% CP complete goat pellet was offered alone (control diet, C) or added (1), or not, as supplement to three grass hays (coastal bermudagrass, CB; Tifton 85 bermudagrass, T; and sorghum-Sudan grass hay, SS), to Boer-cross wethers (n 5 72). The resulting seven diets were offered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Several studies have shown that the nutritional level of diets can affect meat quality and the expression levels of genes associated with meat quality (Patterson et al . ; Hocquette et al . ; Guo et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the nutritional level of diets can affect meat quality and the expression levels of genes associated with meat quality (Patterson et al . ; Hocquette et al . ; Guo et al .…”
Section: Introductionmentioning
confidence: 99%